2011
DOI: 10.1073/pnas.1110518109
|View full text |Cite
|
Sign up to set email alerts
|

Plastid terminal oxidase 2 (PTOX2) is the major oxidase involved in chlororespiration in Chlamydomonas

Abstract: By homology with the unique plastid terminal oxidase (PTOX) found in plants, two genes encoding oxidases have been found in the Chlamydomonas genome, PTOX1 and PTOX2. Here we report the identification of a knockout mutant of PTOX2. Its molecular and functional characterization demonstrates that it encodes the oxidase most predominantly involved in chlororespiration in this algal species. In this mutant, the plastoquinone pool is constitutively reduced under dark-aerobic conditions, resulting in the mobile ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
159
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(168 citation statements)
references
References 37 publications
9
159
0
Order By: Relevance
“…Proteins were transferred onto nitrocellulose filters (BioTrace NT; Pall Corporation) using a semidry apparatus (BIORAD). Primary antibodies were sourced from Michael Hippler (PSAD, LHCSR3, PGRL1, and ANR1; Naumann et al, 2005Naumann et al, , 2007Petroutsos et al, 2009;Terashima et al, 2012), Gilles Peltier (PGRL1; Tolleter et al, 2011), Pierre Cardol (NDA2; Jans et al, 2008), Agrisera (LSU, COXIIb, Psba D1, CF1, and AOX1), and Francis-Andre Wollman (PTOX2 and cyt f; Vallon et al, 1991;Houille-Vernes et al, 2011) and decorated by incubation in Tris-buffered saline. Secondary antibody was anti-rabbit (Invitrogen).…”
Section: Protein Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins were transferred onto nitrocellulose filters (BioTrace NT; Pall Corporation) using a semidry apparatus (BIORAD). Primary antibodies were sourced from Michael Hippler (PSAD, LHCSR3, PGRL1, and ANR1; Naumann et al, 2005Naumann et al, , 2007Petroutsos et al, 2009;Terashima et al, 2012), Gilles Peltier (PGRL1; Tolleter et al, 2011), Pierre Cardol (NDA2; Jans et al, 2008), Agrisera (LSU, COXIIb, Psba D1, CF1, and AOX1), and Francis-Andre Wollman (PTOX2 and cyt f; Vallon et al, 1991;Houille-Vernes et al, 2011) and decorated by incubation in Tris-buffered saline. Secondary antibody was anti-rabbit (Invitrogen).…”
Section: Protein Analysismentioning
confidence: 99%
“…Most of these alternative pathways use molecular oxygen (O 2 ) as a terminal electron acceptor, and their prevalence is even more species dependent than CEF. The plastoquinol terminal oxidase (PTOX) is active in chlororespiration to balance dark chloroplast redox poise and can also work as a valve under specific conditions to oxidize plastoquinols while reducing oxygen when the PQ pool is overreduced (Bailey et al, 2008;Houille-Vernes et al, 2011). The Mehler reaction describes a water-water cycle in which electrons generated by the splitting of water at the donor side of PSII are used to reduce O 2 at the acceptor side of PSI.…”
mentioning
confidence: 99%
“…The alternative oxidases, plastid plastoquinol terminal oxidases PTOX1 and PTOX2, are thought to be involved in the chlororespiration in C. reinhardtii (Rumeau et al, 2007;Bailleul et al, 2010;Houille-Vernes et al, 2011), and changes in protein and transcript abundance have been found to be associated with nutrient deprivation in algae, particularly iron deprivation as well as light stress (Houille-Vernes et al, 2011). PTOX1 and PTOX2 transcripts decreased in abundance 1.5-fold within the first half hour but then increased through 24 h to slightly less or greater than N-replete conditions.…”
Section: Changes In the Levels Of Transcripts And Proteins Of Photosymentioning
confidence: 99%
“…In several plant species, up-regulation of PTOX has been observed in response to adverse conditions, such as exposure to high-light stress in low or elevated temperature environments (Streb et al, 2005) or under salt stress (Stepien and Johnson, 2009). Deletion of the PTOX2 gene in Chlamydomonas reinhardtii, encoding PTOX, confirmed a role in preventing overreduction of the plastoquinone pool in the light (Houille-Vernes et al, 2011). The mutant demonstrated reduced fitness compared with the wild-type under illumination, although growth was not examined under varying environmental conditions.…”
mentioning
confidence: 94%